Comparison of Single-operator Laser-assisted Ultrasound-guided Radial Arterial Cannulation in Young Children with Traditional Ultrasound Guidance: A Randomized Clinical Trial. (14th February 2023) - Hou, Lin; Song, Xuesong; Yan, Na; Zhao, Zhuang; Li, Zhiwen
Abstract : Background: Radial artery cannulation in young children is challenging. A single-operator laser-assisted ultrasound-guidance system was invented to project the path of the target artery on the skin surface. The hypothesis was that this system would improve the first-attempt success rate of radial arterial cannulation in young pediatric patients relative to traditional ultrasound guidance. Methods: This single-center, prospective, parallel-group, randomized controlled study enrolled pediatric patients (n = 80, age less than 2 yr) requiring radial artery cannulation during general anesthesia. The participants were randomized into the traditional ultrasound-guidance group or the single-operator laser-assisted ultrasound-guidance group. After inducing general anesthesia, ultrasound-guided radial artery cannulation was performed by two experienced operators. The primary outcome was the first-attempt success rate. The secondary outcomes included the procedure time to success within the first attempt, midmost rate of first attempt, first needle-tip position, and average number of adjustments. Results: In total, 80 children were included in the analysis. The first-attempt success rate in the single-operator laser-assisted ultrasound-guidance group (36 of 40 [90%]) was significantly greater than that in the traditional ultrasound-guidance group (28 of 40 [70%]; absolute difference, 20% [95% CI, 2.3% to 36.6%]; P = 0.025). The median procedure time to success within the first attempt was shorter in the single-operator laser-assisted ultrasound-guidance group compared with the traditional ultrasound-guidance group (31 s [27, 36 s] vs . 46 s [39, 52 s]; P < 0.001). The incidence of hematoma in the single-operator laser-assisted ultrasound-guidance group (1 of 40, 3%) was significantly lower than that in the traditional ultrasound-guidance group (11 of 40, 28%; P = 0.002). Regarding the initial needle-tip position after skin puncture, the median score (4 [3, 4] vs . 2 [2, 3]; P < 0.001); position 3, 4, or 5 (38 [95%] vs . 13 [33%]; P < 0.001); and position 4 or 5 (26 [65%] vs . 5 [13%]; P < 0.001) were all in favor of single-operator laser-assisted ultrasound guidance. Conclusions: Compared with traditional ultrasound guidance, the single-operator laser-assisted ultrasound-guided system is a useful add-on to the ultrasound dynamic needle-tip puncture technique. It improves the first-attempt success rate of radial artery cannulation in children younger than 2 yr by projecting the path of the artery on the skin and provides better procedural conditions (stable ultrasound probe). Abstract : In this prospective randomized study, laser-assisted ultrasound guidance, projecting the path of the target artery onto the skin surface, improved the speed and the success rate of radial artery cannulation in young children when compared to traditional ultrasound-guided cannulation.